PENULISAN SKENARIO DRAMA BERSETTING SEJARAH UNTUK OSIS SMP MUHAMMADIYAH SUMBANG BANYUMAS - Arifin Suryo Nugroho; Ipong Jazimah (Universitas Muhammadiyah Purwokerto, 2019)
ABSTRACT The problem discussed by partners is the limitations of students in terms of understanding history and making drama scenarios, especially drama scenarios with historical settings. This program aims to support creativity and students in reconstructing a historic event. Reconstruction then continued in making drama scenarios. Writing historical drama scenarios can provide alternative drama performances at school. Another benefit is fostering a sense of nationalism and nationality in students. The method used is training and mentoring. The results of this study are the increasing ability of students in making drama scenarios with historical settings. Keywords: Student Council students, drama scenarios, historical understanding